Gorkhas’ Recruitment into British Army: A Historical Overview - Rai, Ram Prasad (Bon Voyage, 2024)
This article presents a historical overview and analysis of the Gorkhas’ recruitment into the British Army over more than 200 years. The study examines the evolution of the recruitment process, highlighting key periods and changes: the era of the East India Company before 1886, the World War periods, and the present day. The research investigates how the bravery, dedication, and loyalty of Nepalese youths during the Anglo-Nepal Wars (1814-16) led to British authorities encouraging Gorkhali youths to join the British Army, aiming to leverage their skills for future wars and imperial expansion. Despite their valor, Gorkhas faced numerous challenges, and significant improvements in recruitment conditions did not occur until after 1886. Even then, parental consent was a significant barrier. It was not until the 1970s that Gorkha youths openly expressed a desire to join, but by then, the selection process had become much tougher due to decreased demand for their services. Employing a qualitative research approach, the article utilizes a variety of sources including books on Britain-Nepal military relations, journal articles, periodicals, and war history books from Nepal, Britain, and other relevant regions to provide a comprehensive analysis. The study’s findings indicate that the recruitment process was particularly challenging before 1886 and during the World Wars, despite a high demand for Gorkha soldiers. In the present day, while the recruitment process is more transparent, opportunities for Gorkhas have significantly diminished due to a reduced demand for their services.